2021
DOI: 10.21203/rs.3.rs-742064/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation, Characterization, and Biodistribution of Glutathione PEGylated Nanoliposomal Doxorubicin for Brain Drug Delivery with A Post-insertion Approach

Abstract: Brain cancer treatments have been largely unsuccessful due to the blood-brain barrier. Several publications support the presence of glutathione (GSH) receptors on the surface of the BBB and consequently the products such as the 2B3-101, which is almost 5% pre-inserted GSH PEGylated liposomal doxorubicin, is under process in clinical studies. Here we conducted the PEGylated nanoliposomal doxorubicin particles that are covalently attached to the glutathione using the post-insertion technique. The post-insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…The distribution of the medications in the blood showed that their concentration decreased after 2 days, possibly due to their accumulation in other tissues, particularly the liver and spleen. This result is consistent with prior research, which found that drug distribution into the blood was dramatically reduced after 2‐ or 3‐days post‐injection [ 24 , 28 , 57 ]. The higher distribution of pre‐ and post‐inserted formulations in the liver and spleen seemed to be due to the presence of the reticuloendothelial system (RES), which was able to rapidly take up the formulations and resulted entrapment in the mentioned organs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The distribution of the medications in the blood showed that their concentration decreased after 2 days, possibly due to their accumulation in other tissues, particularly the liver and spleen. This result is consistent with prior research, which found that drug distribution into the blood was dramatically reduced after 2‐ or 3‐days post‐injection [ 24 , 28 , 57 ]. The higher distribution of pre‐ and post‐inserted formulations in the liver and spleen seemed to be due to the presence of the reticuloendothelial system (RES), which was able to rapidly take up the formulations and resulted entrapment in the mentioned organs.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that this method is simple, cost-effective and reproducible when generating actively targeted liposomal DOX [25][26][27]. Similarly, in our previous work, using the post-insertion method, we demonstrated that GSH-targeted liposomes penetrated the BBB efficiently [28].…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The mean size, charge and PDI of PEG-nanoliposomes loaded with oleu (PEG-oleu) were 129.35 nm, À9.55 mV and 0.1010, respectively. All size, charge and PDI results at time 0, 24, and 48 h and 1 week are within the optimum nanoliposome values(Mehrabian et al, 2022). In addition, one-way ANOVA was performed to investigate the impact of storage time at 4 C on nanoliposome characterization, as shown in Table4.…”
mentioning
confidence: 85%